Some aspects of mechanisms of NaCl stress tolerance in the seedlings of four rice genotypes - Alamgir, ANM; Musa, Mohammad; Ali, Mohammad Yousuf (Bangladesh Journal of Botany, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Biomass production under salt stress decreased with the sequence: IRATOM-24 > BR 9 > Nonabokra > Pokkali. In Pokkali root-shoot dry wt. was less affected and it maintained high root to shoot ratio (R/S) and their tolerance indices (TI). Salinity stress increased Na+, Cl- and decreased K+ and Ca+ contents and consequently their ratios in both root and shoot of the seedlings. Under stress proline level was increased in both root and shoot of the seedlings in all genotypes, the highest was observed in the root of Pokkali and in the shoot of IRATOM-24. Excepting BR 9 salinity increased protein content in other genotypes and among them Nonabokra maintained the highest protein level. Salinity inhibited the root ATPase activity in all except Pokkali. Efficiency of the maintenance of relatively high dry matter, R/S ratio, essential ions, K+ - Ca2+/ Na+ ion ratios, proline and protein contents in the seedlings including the root ATPase activity may be imp ortant aspects of NaCl stress tolerance mechanism as found in one or another rice genotype of the present work. Â Key words: Salinity, Stress tolerance, Proline, Protein, ATPase activity DOI = 10.3329/bjb.v36i2.1510 Bangladesh J. Bot. 36(2): 181-184, 2007 (December)